1999
DOI: 10.1038/sj.bjc.6690153
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor expression in male breast carcinoma: lack of clinicopathological association

Abstract: Summary Androgen receptor (AR) expression was retrospectively analysed in 47 primary male breast carcinomas (MBCs) using a monoclonal antibody on formalin-fixed, paraffin-embedded tissues. AR immunopositivity was detected in 16 out of 47 (34%) cases. No association was found with patient age, tumour stage, progesterone receptor (PGR) or p53 protein expression. Well-differentiated MBCs tended to be AR positive more often than poorly differentiated ones (P = 0.08). A negative association was found between ARs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
32
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 42 publications
(55 reference statements)
9
32
2
2
Order By: Relevance
“…Unlike other studies on FBC or MBC, we found no correlation between AR and ER/PR status (14,23). There was no association between AR and age, tumour size, histological grade and HER2 status, and these results are in accordance with those in reports on FBC and MBC as well (12,14,23). However, the AR expression rate was found to be significantly higher in cases with lymph node metastases, suggesting that AR-positive MBC tends to be more aggressive than AR-negative MBC.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Unlike other studies on FBC or MBC, we found no correlation between AR and ER/PR status (14,23). There was no association between AR and age, tumour size, histological grade and HER2 status, and these results are in accordance with those in reports on FBC and MBC as well (12,14,23). However, the AR expression rate was found to be significantly higher in cases with lymph node metastases, suggesting that AR-positive MBC tends to be more aggressive than AR-negative MBC.…”
Section: Discussionsupporting
confidence: 76%
“…The AR expression rate was 40.2% in this study, a value that was similar to that reported by other investigators (12,14), but much lower than that reported in FBC patients (22). Compared with women, men usually have lower oestrogen and higher androgen levels.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A study on a series of 75 patients showed that 5% of male breast cancers over expressed HER2 (12) . The role of androgen receptors is unclear and has no consequences on the prognosis of male breast cancer (13,14) . In our case, the histological find an invasive breast carcinoma no special type (NST) grade II of SBR.…”
Section: Discussionmentioning
confidence: 99%
“…Pacheco et al (30) reported that 75% of the male breast tumors in their study were AR positive. Pich et al (31) found that, of the 47 male breast tumors examined, 34% were AR positive and that well-differentiated tumors were AR positive more often than the poorly differentiated tumors. Munoz de Toro et al (32) reported that 38.5% of male breast tumors in their study were AR positive and that tumors from younger patients showed a significant lack of AR expression.…”
mentioning
confidence: 99%